Blockchain-powered wireless sensor networks: enhancing security and privacy in the IoT era - Ibrahim Mekawy (Big Data and Computing Visions)
Nowadays, we know that Wireless Sensor Networks (WSNs) are being widely applied in many fields of human life such as civil and military applications. WSNs are broadly applied for various applications in tracking and surveillance due to their ease of use and other distinctive characteristics compelled by real-time cooperation among the Sensor Nodes (SNs). When applying the WSN in the real world we have to face many challenges such as security, and storage due to its centralized server/client models. Although WSNs can bring a lot of benefits and conveniences. This paper discusses an in-depth survey of a blockchain-based approach for malicious node detection, an exhaustive examination of the integration of blockchain techniques with WSNs (BWSN), and insights into this novel concept.